2020
DOI: 10.21203/rs.2.21214/v1
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Characteristics and outcomes of Stanford type A aortic dissection patients with post-operation severe hyperbilirubinemia: a retrospective cohort study

Abstract: Objective Hyperbilirubinemia is one of the common complications after cardiac surgery and is associated with increased mortality. However, to the best of our knowledge, the report on clinical significance of postoperative severe hyperbilirubinemia in Stanford type A aortic dissection (AAD) patients is limited. Therefore, the purpose of our present study is to assess the characteristics and outcomes of AAD patients with post-operation severe hyperbilirubinemia.Methods Patients who underwent surgical treatment f… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
3
0

Year Published

2021
2021
2022
2022

Publication Types

Select...
1
1

Relationship

1
1

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 21 publications
(31 reference statements)
1
3
0
Order By: Relevance
“…The hemolysis occurs and bilirubin is increasing gradually during CPB [16]. The postoperative peak total bilirubin level was at the second or third day after aortic arch surgery [4,13], which was consistent with our study (data was not shown). Furthermore, although the majority of AKI occurs within the rst 2-3 postoperative days according to the increase of sCr [17], diagnosis of the AKI delays using the elevation of sCr owing to the rate-limiting step of sCr production and release by skeletal muscle [18].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…The hemolysis occurs and bilirubin is increasing gradually during CPB [16]. The postoperative peak total bilirubin level was at the second or third day after aortic arch surgery [4,13], which was consistent with our study (data was not shown). Furthermore, although the majority of AKI occurs within the rst 2-3 postoperative days according to the increase of sCr [17], diagnosis of the AKI delays using the elevation of sCr owing to the rate-limiting step of sCr production and release by skeletal muscle [18].…”
Section: Discussionsupporting
confidence: 91%
“…The ischemia and reperfusion is considered to be the main reason for AKI and other factors may exacerbate AKI [3]. Hyperbilirubinemia (HB) remains a prevalent postoperative complication in aortic arch surgery [4].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…1 Post-cardiac surgery hyperbilirubinemia is common, with an incidence of about 20–51%, 27 which may result from factors associated with cardiopulmonary bypass (CPB), such as hemolysis, hypoperfusion, and systemic inflammatory response, and also may be associated with secondary hepatic dysfunction due to heart failure or sepsis. 4,8 Post-cardiac-surgery hyperbilirubinemia is associated with longer hospital stay and a mortality of up to 30%. In patients with hepatic failure after cardiac surgery, the in-hospital mortality could be as high as 90%.…”
Section: Introductionmentioning
confidence: 99%